2019
DOI: 10.5296/jei.v5i2.15683
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Involvement Level of 40 and Over Aged Individuals

Abstract: This study aimed to investigate the leisure involvement level of individuals 40 years and over according to various variables. The study sample consisted of 106 volunteers aged 40 years and over in Hendek district of Sakarya city. As a data collection tool "leisure involvement scale" which developed by Kyle et al. (2007) and adapted to Turkish by Gürbüz et al. (2015), and personal information form were used. SPSS statistic program was used to analyze the data. The histograms, Skewness, and Kurtosis values (bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In this context, it can be said that females participating in physical activity had higher levels of involvement in the activity in which they participate than males. The results of studies conducted by Chen et al [38], Ekinci and Yalçın [7], Chang [8], and emirel [45] were parallel with the results of this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this context, it can be said that females participating in physical activity had higher levels of involvement in the activity in which they participate than males. The results of studies conducted by Chen et al [38], Ekinci and Yalçın [7], Chang [8], and emirel [45] were parallel with the results of this study.…”
Section: Discussionsupporting
confidence: 88%
“…It was determined that there was no statistically significant relationship between the ages of the individuals and their leisure involvement. In the study conducted by Ekinci and Yalçın [7] on leisure Involvement of individuals aged 40 and over, no difference between the individuals' leisure involvement according to their ages was determined. It was found that there was no significant relationship between age and the perceived freedom in leisure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation